Upregulated LncRNA-LINC00659 expression by H. pylori infection promoted the progression of gastritis to cancer by regulating PTBP1 expression - Jiani Zhang; Zhengbo Zhang; Danlei Shen (Wolters Kluwer Medknow Publications, 2024)
Context: Helicobacter pylori (H. pylori), a spiral-shaped bacterium, is closely associated with chronic, progressive gastric mucosal damage, gastric atrophy, and even gastric cancer (GC). An increasing number of studies have addressed the correlation between long noncoding RNAs (lncRNAs) and H. pylori pathogenicity in GC. Objective: In this study, we found that the expression level of LINC00659 gradually increased in the progression from atrophic gastritis, intestinal metaplasia, and dysplasia to GC in H. pylori-infected patients. Thus, we aimed to further explore the function of LINC00659 in the progression of gastritis to cancer under H. pylori infection. Materials and Methods: StarBase predictions, ribonucleic acid (RNA)-binding protein immunoprecipitation assays, and gene ontology functional annotation (GO)/Kyoto encyclopedia of genes and genomes (KEGG) pathway analysis were performed to identify the RNA-binding proteins of LINC00659; moreover, qRT‒PCR, western blotting, RNA interference, and immunofluorescence assays were used to investigate the function of LINC00659. Results: LINC00659 bound directly to the RNA-binding protein polypyrimidine tract-binding protein (PTBP1). Importantly, qRT‒PCR and western blot assays demonstrated that PTBP1 expression increased in the progression from inflammation to cancer in the stomach of H. pylori-infected patients and H. pylori-infected GES-1 cells. However, LINC00659 knockdown downregulated PTBP1 expression and inhibited PTBP1 binding under H. pylori infection. Finally, LINC00659 knockdown significantly reduced H. pylori-induced human gastric epithelial cell senescence and suppressed interleukin (IL)-6 and IL-8 secretion by reducing the phosphorylation level of NF-κB p65. Conclusions: This study indicated that LINC00659 may have the potential to be a novel promising prognostic and therapeutic marker for H. pylori-associated gastric diseases.